GOCE, la Ferrari dei satelliti - Bernardini, Fabrizio (GEOmedia, 2009)
GOCE, a "Ferrari" between satellites GOCE is a new exciting European Space Agency mission within the Living Earth programme. The design of the satellite and its sensor, the Electrostatic Gravity Gradiometer, are intimately linked to produce the most advanced geodetical satellite ever put into orbit. The main result of GOCE will be the accurate mapping of the Earth's gravitational field to provide insight into the geoid as close up as 1-2 centimetres. Additional application will be applicable to studies of ocean circulation and continental drift.